Lift - Lê, Minh, 1979- (Disney Hyperion, 2020)
From the award-winning and bestselling creators of Drawn Together comes the fantastic tale of a magical elevator that will lift your spirits--and press all the right buttons! Iris loves to push the elevator buttons in her apartment building, but when it's time to share the fun with a new member of the family, she's pretty put out. That is, until the sudden appearance of a mysterious new button opens up entire realms of possibility, places where she can escape and explore on her own. But when she's forced to choose between going at it alone or letting her little brother tag along, Iris finds that sharing a discovery with the people you love can be the most wonderful experience of all. Using their dynamic comics-inspired storytelling, acclaimed author Minh Lê and Caldecott Medal-winning artist Dan Santat carry readers on a journey of ups, downs, and twists and turns that will send hearts--and imaginations--soaring.